Modelling agricultural land abandonment in a fine spatial resolution multi-level land-use model: An application for the EU. (February 2021) - Perpiña Castillo, Carolina; Jacobs-Crisioni, Chris; Diogo, Vasco; Lavalle, Carlo
Abstract: In the majority of EU Member States, agricultural land is expected to decrease not only due to land-use changes in favour of urban expansion and afforestation but also to land abandonment processes. The knowledge on location and extent of agricultural land abandonment is relevant for estimating local external effects and adapting policy interventions. Currently, multi-level land-use models are able to capture determined processes of demand-driven redevelopment. However, land abandonment is much more difficult to capture because of its more ambiguous definition and the lack of data on its spatial distribution. This paper presents a method to explicitly model agricultural abandonment as a choice of disinvestment, which in turn is embedded in a utility-based land-use modelling framework that projects land-use changes for the EU and the UK. Validation exercises using observed spatial distribution of abandoned farmland show that the proposed method allows to model abandonment with acceptable accuracy. Highlights: LUISA is a modelling platform able to dynamically project agricultural land abandonment. Biophysical, agricultural socio-economic and regional factors are key drivers to estimate abandonment risk. The model outcomes project more than 5.6 M ha of abandoned land by 2030 in the EU and the UK. Risk areas for land abandonment are widespread in the EU countries and not limited to mountain regions. We present a long-term territorial assessment that might guide different strategies for preventing land abandonment. Data availability and resolution are key elements for modelling and validating farmland abandonment.